2021
DOI: 10.1021/acsanm.1c01713
|View full text |Cite
|
Sign up to set email alerts
|

Alkali-Assisted Hydrothermal Exfoliation and Surfactant-Driven Functionalization of h-BN Nanosheets for Lubrication Enhancement

Abstract: Intrinsic low shear strength, excellent mechanical properties, and high thermal conductivity of two-dimensional h-BN nanomaterials make them promising alternatives to conventional metal-/phosphorus-/sulfur-based additives for the development of eco-friendly lubricant formulation. However, the poor dispersibility of h-BN nanomaterials in lubricating oils is a major challenge. Herein, a facile approach of strong alkali-assisted hydrothermal exfoliation and defect-sensitive etching of h-BN powder is demonstrated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…The random organization of the WS 2 −O-OES nanosheets in aggregates diminished the lowshearing properties and increased the coefficient of friction. 63 Thus, a 200 ppm dose is considered as an optimized dose for further tribo-evaluation experiments. The worn scars developed on steel balls after each tribo-test were measured to estimate the wear properties.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The random organization of the WS 2 −O-OES nanosheets in aggregates diminished the lowshearing properties and increased the coefficient of friction. 63 Thus, a 200 ppm dose is considered as an optimized dose for further tribo-evaluation experiments. The worn scars developed on steel balls after each tribo-test were measured to estimate the wear properties.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Further increasing the dose of WS 2 –O-OES nanosheets (300 ppm) showed a higher coefficient of friction, and it could be due to aggregation at a higher concentration under the tribological condition. The random organization of the WS 2 –O-OES nanosheets in aggregates diminished the low-shearing properties and increased the coefficient of friction . Thus, a 200 ppm dose is considered as an optimized dose for further tribo-evaluation experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Another interesting method is the introduction of quaternary ammonium salts to tune the properties of poorly dispersible h-BN in the base oil. One typical study investigated the tribological performance of a modified h-BN by the grafting of cetyltrimethylammonium bromide (h-BN-CTAB) via hydrothermal processing, 187 which showed that the addition of h-BN-CTAB in SN-150 mineral oil significantly enhanced the friction-reducing and antiwear properties, paving the way for the scalable synthesis of chemically functionalized h-BN nanosheets for the development of new-generation lubricant formulations. Moreover, it has been revealed that the defect sites on h-BN are capable of improving the reaction efficiency with alkylamines, 188 which dramatically affected the comprehensive performance of h-BN, including the length of alkylamine chains and the number of branched chains.…”
Section: Excellent 2d Nanomaterials For Lubricating Additivesmentioning
confidence: 99%
“…16 However, the use of cetyl trimethyl ammonium bromide (CTAB), a cationic surfactant with outstanding surface activity and dispersion, can effectively reduce the coefficient of friction, wear, and heat loss, as well as enhance the lubrication effect. 26 Furthermore, CTAB possesses antirust, antioxidation, anticorrosion, and other properties that can increase the lubricant's service life and stability. 27 Considering its numerous benefits and cost-effectiveness, CTAB is an ideal candidate for TiO 2 modification and construction of the TiO 2 @CTAB core−shell structure of marine diesel engines.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis methods for nanoparticles can be divided into solid-phase reactions, liquid-phase reactions, gas-phase reactions, and mechanical blending, based on various principles . However, the use of cetyl trimethyl ammonium bromide (CTAB), a cationic surfactant with outstanding surface activity and dispersion, can effectively reduce the coefficient of friction, wear, and heat loss, as well as enhance the lubrication effect . Furthermore, CTAB possesses antirust, antioxidation, anticorrosion, and other properties that can increase the lubricant’s service life and stability .…”
Section: Introductionmentioning
confidence: 99%